2016
DOI: 10.5958/2277-8934.2016.00023.0
|View full text |Cite
|
Sign up to set email alerts
|

A systemic review on ultrasonographic applications in camels

Abstract: Ultrasound is widely accepted as a safe noninvasive diagnostic imaging technique in animals and human. This review aims to shed light on the current applications and future prospect of ultrasonography in camels. To date, ultrasonography has been used efficiently to study the ovarian status in she camels such as; follicular wave, spontaneous ovulation, optimum time for mating, ovarian vasculature, superovulatory response, ovarian follicular dynamics, ovarian follicular wave synchronisation and follicular deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 45 publications
4
8
0
4
Order By: Relevance
“…Similar changes in the hormonal levels were observed during pregnancy, parturition and postpartum in llama [20,21] . The ultrasonographic examination was performed twice previous studies by Abu-Seida [22] , Derar, Ali [23] , who found that the uterine involution was completed in female camels from 25 th until 30 th days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes in the hormonal levels were observed during pregnancy, parturition and postpartum in llama [20,21] . The ultrasonographic examination was performed twice previous studies by Abu-Seida [22] , Derar, Ali [23] , who found that the uterine involution was completed in female camels from 25 th until 30 th days postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…direkt anliegenden echogenen Saum begrenzt ist. Die letztgenannte Linie stellt die Grenzfläche zum darunterliegenden Bindegewebe der Unterhaut dar 4 . Das sonografische Erscheinungsbild des Sohlenhorns beim Kamel ist kaum unterschiedlich zu dem des Rindes 12 17 19 20 .…”
Section: Diskussionunclassified
“…In Mitteleuropa werden Kamele aufgrund ihrer sehr geringen Verbreitung selten wegen orthopädischer Erkrankungen vorgestellt. Werden allerdings Kamele wegen Lahmheit präsentiert, dann liegen häufig pathologische Veränderungen an der Sohle als Ursache vor [4]. Abszesse unter dem Sohlenhorn (eitrige Pododermatitis) sind bei vielen Tierarten als häufige Ursache für eine akute Stützbeinlahmheit beschrieben worden, so beispielsweise bei Pferd und Rind [7][8][9][10][11] sowie auch bei Neuweltkamelen [12].…”
Section: Diskussionunclassified
See 2 more Smart Citations